Associação entre a área de superfície periodontal inflamada e proteína C reativa no soro de pacientes sob terapia de hemodiálise - Schöffer, Caroline (2019)
Aim: to evaluate the periodontal status of patients with chronic kidney disease on hemodialysis and to verify the association of inflamed periodontal surface area (PISA) with C-reactive protein levels. Methods: A cross-sectional study with 176 patients on regular hemodialysis was interviewed and submitted to a complete periodontal examination. Index of visible plaque (VPI), gingival bleeding index (GBI), dental calculus (DC), probing pocket depth (PPD), clinical attachment level (CAL), bleeding probing (BOP) were evaluated. Periodontal parameters were used to obtain PISA. Serum levels of high sensitivity C-reactive protein (hsCRP) were collected. Logistic regression was used to model the association between PISA and hsCRP. Results: The prevalence of periodontal disease was 98.9%; in its more advanced stages (III and IV), this prevalence was 26.1% and 52.8%. Our results show a statistically significant association between PISA and hsCRP (OR = 2.99; 95% CI = 1.11 - 8.0). Conclusion: Greater areas of inflamed periodontal surface are associated with higher hsCRP levels.